2009
DOI: 10.1093/ndt/gfp423
|View full text |Cite
|
Sign up to set email alerts
|

Impact of renal function on coronary plaque composition

Abstract: Impaired renal function was related to higher percentage of lipid volume and lower percentage of fibrous volume in coronary plaque. Our findings may explain the increasing risk of cardiovascular events in patients with renal dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
31
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 34 publications
3
31
1
Order By: Relevance
“…We previously demonstrated that patients with CKD had larger lipid profiles and a higher prevalence of plaque disruption compared with patients without CKD, although we found no significant difference in FCT at the thinnest portion across groups 31. Using integrated backscatter intravascular ultrasonography, Miyagi et al demonstrated that coronary plaques in patients with CKD had greater lipid and less fibrous tissue volume in 89 patients with stable angina 32. Hayano et al further demonstrated that lower eGFR levels were associated with greater lipid and lower fibrous content 33.…”
Section: Discussioncontrasting
confidence: 49%
“…We previously demonstrated that patients with CKD had larger lipid profiles and a higher prevalence of plaque disruption compared with patients without CKD, although we found no significant difference in FCT at the thinnest portion across groups 31. Using integrated backscatter intravascular ultrasonography, Miyagi et al demonstrated that coronary plaques in patients with CKD had greater lipid and less fibrous tissue volume in 89 patients with stable angina 32. Hayano et al further demonstrated that lower eGFR levels were associated with greater lipid and lower fibrous content 33.…”
Section: Discussioncontrasting
confidence: 49%
“…Recently, IB-IVUS has added to perform analysis of the tissue components of coronary plaque in vivo, 3 and studies using this technique have revealed that patients with coronary risk factors including high insulin levels, metabolic syndrome, diabetes, and/or chronic kidney disease have a high prevalence of lipid-rich coronary plaque. 24, 25 It is well established that high serum levels of LDL-C constitute a strong predictor of CHD, and that LDL-C-lowering therapy reduces CHD. 26 The LDL-C/HDL-C ratio was found to be a more accurate in determining CHD risk, compared to LDL-C or HDL-C alone.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the impact of pioglitazone on atheroma volume depends not only on the hypoglycemic effect but also on reduction in the levels of inflammatory biomarkers, triglycerides, and elevation of HDL-C. 31 It has been reported that renal dysfunction is associated with severity of coronary atherosclerosis 32 and higher proportion of lipid volume. 33 Furthermore, risk of cardiac events was associated with eGFR and the presence of DM. 34 Consistent with previous findings, significant negative correlations were observed between atheroma volume at follow-up and eGFR, and FF volume at follow-up tended to be negatively correlated with eGFR in the present study.…”
Section: Discussionmentioning
confidence: 98%